2023
DOI: 10.3892/mmr.2023.12934
|View full text |Cite
|
Sign up to set email alerts
|

ASK1 inhibitor NQDI‑1 decreases oxidative stress and neuroapoptosis via the ASK1/p38 and JNK signaling pathway in early brain injury after subarachnoid hemorrhage in rats

Abstract: oxidative stress and neuroapoptosis are key pathological processes after subarachnoid hemorrhage (Sa H ). T he present st udy eva luated t he anti-oxidation and anti-apoptotic neuroprotective effects of the apoptosis signal-regulating kinase 1 (aSK1) inhibitor ethyl-2,7-dioxo-2,7-dihydro-3H-naphtho(1,2,3-de) quinoline1-carboxylate (nQdi-1) in early brain injury (eBi) following SaH in a rat model. a total of 191 rats were used and the SAH model was induced using monofilament perforation. Western blotting was su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…This partly explains the beneficial effects of lycopene on fibrosis and inflammation, which may be attributed to its influence on the TRAF6-ASK1 complex. A prior study has indicated that NQDI-1 can inhibit the activation of the ASK1 and JNK signaling pathways in the brains of rats with subarachnoid hemorrhage . It is interesting that the suppression of ASK1 activity can reverse the impacts of lycopene on NASH in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This partly explains the beneficial effects of lycopene on fibrosis and inflammation, which may be attributed to its influence on the TRAF6-ASK1 complex. A prior study has indicated that NQDI-1 can inhibit the activation of the ASK1 and JNK signaling pathways in the brains of rats with subarachnoid hemorrhage . It is interesting that the suppression of ASK1 activity can reverse the impacts of lycopene on NASH in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…A prior study has indicated that NQDI-1 can inhibit the activation of the ASK1 and JNK signaling pathways in the brains of rats with subarachnoid hemorrhage. 58 It is interesting that the suppression of ASK1 activity can reverse the impacts of lycopene on NASH in vitro. It suggests that the effects of lycopene on hepatic lipid regulation are dependent on the inhibition of ASK1, thereby improving ER stress.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Identifying therapeutics that minimize Mitochondrial dysfunction occurs due to susceptibility to hypoxia and ischemic injury resulting in the release of ROS, further amplifying oxidative stress and stimulating the mitochondrial apoptotic pathway [46]. Identifying therapeutics that minimize oxidative stress and mitochondrial apoptosis is critical for improving the prognosis and management of TBIs [47]. MitoQ is an antioxidant that crosses the blood-brain barrier and can accumulate within mitochondria [43].…”
Section: Traumatic Intracranial Hemorrhagementioning
confidence: 99%